Dampak Pemberian Tunjangan Tambahan Serta Komitmen Guru Terhadap Kinerja Guru di MI Al-Ittihad Kalianyar Jogoroto Jombang - Lailatus Sa’adah; Tadzarikuz Zaman (Populer: Jurnal Penelitian Mahasiswa, 2024)
In building good teacher performance, it is necessary to provide additional allowances to improve teacher welfare. This will lead to teacher commitment in educating. This study aims to determine the impact of providing additional allowances and commitment on teacher performance. The research location is at MI Al-Ittihad Kalianyar Jogoroto Jombang using qualitative research that relies on observations, interviews, and documentation on the object of research so as to produce data that describes in detail. With the results of the study that the provision of additional allowances provided by the principal at MI Al-Ittihad Kalianyar Jogoroto Jombang has an impact on improving teacher performance such as teachers willing to work overtime to do the tasks given by the school. In addition, the commitment of teachers at MI Al-Ittihad Kalianyar Jogoroto Jombang is high and can be seen by the enthusiasm and activity of the teachers in carrying out various ideas in the learning process..